Burundi : Sixth Review Under the Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria; Staff Report; Staff Supplement; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burundi. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Burundi showed commendable performance owing to its prudent macroeconomic policies and ambitious structural reforms under the Poverty Reduction and Growth Facility (PRGF). Executive Directors appreciated its macroeconomic stability, strong fiscal discipline, and prudent monetary policies in support of low inflation objectives. They emphasized the need to reduce poverty, sustain macroeconomic stability, and strengthen implementation of structural reforms in reaching the MDGs. They appreciated the efforts taken to deepen implementation of the Poverty Reduction Strategy Paper (PRSP), which offers a framework for the diversification of growth and exports, the improvement of public finance management, and the integration of the regional and global economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet